ADOLESCENTS AND VIOLENCE: A SYSTEMATIC REVIEW OF PROTECTIVE AND RISK FACTORS - Flavia-Elena CIURBEA; Valentina MARINESCU; Anda-Anca RODIDEAL; Alexandra-Elena NEAGU; Cornelia RADA (Anthropological Researches and Studies)
Objectives. The objective of the study was to identify the most common predictors and protective factors regarding juvenile violence as revealed by the scientific literature. Material and methods. Information was searched in the APA PsycNet and PubMed platforms. Longitudinal studies were chosen, which evaluated potential risk or protective factors in violent manifestation and whose samples had an average age of 14-21 years at the time of the violence risk assessment. 39 papers that met the inclusion criteria were retained. Results. The main classes of risk factors were family difficulties: family violence, parent-child conflicts, etc.; individual psychological triggering factors like: anger, low self-control, etc.; history of victimization; school problems: learning difficulties, negative models in school, etc.; substance use; early violent manifestation; the negative influence of the neighborhood. The major categories of the protective factors referred to the favorable family climate: parental involvement, connection with parents, etc.; the presence of beneficial individual psychological factors: emotional well-being, high levels of emotional regulation, etc.; the existence of a positive school climate: school satisfaction, school connectedness, etc. Certain factors were significant only for girls (e.g., religiosity as a protective factor, somatic complaints as a risk factor), and others were significant only for boys (e.g., carrying weapons to school as a risk factor, parental monitoring as a protective factor). Conclusions. Family, individual psychological, and school factors can have both a predictive and a protective role in violence. Amplifying the beneficial dimensions of these factors may contribute to reducing the risk of antisocial behaviors among adolescents.